Achieving 1.2 fm/Hz1/2 Displacement Sensitivity with Laser Interferometry in Two-Dimensional Nanomechanical Resonators: Pathways towards Quantum-Noise-Limited Measurement at Room Temperature. (1st February 2023) - Zhu, Jiankai; Wang, Luming; Wu, Jiaqi; Liang, Yachun; Xiao, Fei; Xu, Bo; Zhang, Zejuan; Fan, Xiulian; Zhou, Yu; Xia, Juan; Wang, Zenghui
Abstract : Laser interferometry is an important technique for ultrasensitive detection of motion and displacement. We push the limit of laser interferometry through noise optimization and device engineering. The contribution of noises other than shot noise is reduced from 92.6% to 62.4%, demonstrating the possibility towards shot-noise-limited measurement. Using noise thermometry, we quantify the laser heating effect and determine the range of laser power values for room-temperature measurements. With detailed analysis and optimization of signal transduction, we achieve 1.2 fm/Hz 1/2 displacement measurement sensitivity at room temperature in two-dimensional (2D) CaNb2 O6 nanomechanical resonators, the best value reported to date among all resonators based on 2D materials. Our work demonstrates a possible pathway towards quantum-noise-limited measurement at room temperature.